National Rivalry among Hospitallers? - Karl Borchardt (Medievalista)
The medieval Hospitaller priory of Bohemia was riven by ethnic divisions and mutually unintelligible languages. The prior’s lieutenant for Austria, Styria, Carinthia and Carniola, who often resided at the important commandery of Mailberg, could have been a nucleus for Austrian independence from Bohemia. The paper edits and discusses a document from 1392 where the prioral chapter deals with a quarrel between Hospitallers in Austria and Styria; their fellow-Hospitallers from the lands of the Bohemian crown (Bohemia proper, Moravia, Silesia) carefully avoided to be offend Duke Albert III of Austria. In the following decades tensions between two rival Habsburg lines in Austria and Styria weakened the position of the Hospitaller lieutenants for the Habsburg lands, especially during the Hussite wars. After the reunification of the Habsburg lands in the early 1460s the commandery of Mailberg was given by Emperor Frederick III and his son Maximilian to their courtiers and creditors, some of whom were not even Hospitallers. With papal support Frederick III tried to transfer Mailberg to his newly-founded military-religious order of St. George at Millstatt in Carinthia. But when the Habsburg rulers became kings of Bohemia and Hungary in 1526, they ceased to be interested in splitting up the Hospitaller priory of Bohemia. In the early modern period this proved to be more important for the future of the priory than “proto-national” identities.